228k views
2 votes
What is 5x - 9 = 3x + 3 ? ​

1 Answer

3 votes

Answer:

= 6

Explanation:

Add 9 9 9 to both sides of the equation 5 − 9 = 3 + 3

5x-9=3x+3 5x−9=3x+3 5 − 9 + 9 = 3 + 3 + 9

Add the numbers

5=3+12

Subtract

3

3x3x

from both sides of the equation

5=3+12

5x=3x+125x=3x+12

5−3=3+12−3

Simplify

Combine like terms

2=12

Divide both sides of the equation by the same term

2=12

2x=122x=12

22=122

Cancel terms that are in both the numerator and denominator

Divide the numbers

=6

User Samuele Mattiuzzo
by
4.5k points